2018
DOI: 10.1080/16549716.2018.1491114
|View full text |Cite
|
Sign up to set email alerts
|

Social support factors associated with psychological resilience among women survivors of intimate partner violence in Gauteng, South Africa

Abstract: Background: Women’s experiences of intimate partner violence (IPV) increase their risk for mental ill health. However, some women exposed to IPV and adversity are psychologically resilient and function well despite these exposures. Objectives: We conducted a study to investigate the factors that are associated with psychological resilience among abused women, using data collected in a household survey conducted in Gauteng province of South Africa. Methods: Data is from a cross-sectional study. A multi-stage ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 58 publications
0
55
1
1
Order By: Relevance
“…Most participants also stated alcohol abuse and poverty as factors that caused violence in relationships. Studies by other authors have found similar results (Machisa et al, 2018;Sabri et al, 2019;Eric Y. Tenkorang, Owusu, Yeboah, & Bannerman, 2013) as factors that led to intimate partner violence. In most cultures, men control and dominate their partners in Ghana (Dickson et al, 2020;Issahaku, 2015;Owusu-Addo et al, 2018;E.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Most participants also stated alcohol abuse and poverty as factors that caused violence in relationships. Studies by other authors have found similar results (Machisa et al, 2018;Sabri et al, 2019;Eric Y. Tenkorang, Owusu, Yeboah, & Bannerman, 2013) as factors that led to intimate partner violence. In most cultures, men control and dominate their partners in Ghana (Dickson et al, 2020;Issahaku, 2015;Owusu-Addo et al, 2018;E.…”
Section: Discussionmentioning
confidence: 52%
“…The feminist theories have also made their argument that defined gender roles within patriarchal societies in addition to men's systematic efforts to control women through the use of power and domination are the major causes or factors of IPV (Bell & Naugle, 2008;Pinto et al, 2010). This finding also collaborates with Machisa et al (2018) and Mann and Takyi (2009) when they made similar findings in their studies. Again, some of the participants identified peer influence as one of the factors that can lead to violence in intimate partner relationships (Elgar et al, 2015;Fleming et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…3 This is an underestimate as under-reporting of rape to the police is a well-known phenomenon. 4 , 5 The extent of rape in South Africa can also be gleaned from perpetration prevalence studies of men where between 28.0% and 37.0% of men disclosed rape perpetration. Studies of women found one in four reported experiences of sexual violence in their lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of women found one in four reported experiences of sexual violence in their lifetime. 5 , 6 , 7…”
Section: Introductionmentioning
confidence: 99%